1995
DOI: 10.1111/j.1476-5381.1995.tb16661.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 5‐HT receptor agonists on depolarization‐induced [3H]‐noradrenaline release in rabbit hippocampus and human neocortex

Abstract: 1 The present study attempted to determine whether noradrenaline (NA) NA release were investigated. 3 In rabbit hippocampus, 5-HT, 5-carboxamidotryptamine (5-CT; 32 pM) and 2-CH3-5-HT (32 pM) increased [3H]-NA release elicited with 360 pulses/3 Hz. Facilitation of transmitter release was not influenced by the 5-HT3 receptor antagonist, tropisetron but was prevented by the a2-adrenoceptor antagonist, rauwolscine. When autoinhibition was avoided by stimulating the tissue with 4 pulses/100 Hz (pseudo-one pulse-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
1

Year Published

1997
1997
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Different studies have reported the occurrence of an interaction between adrenergic and serotonergic mechanisms in the central nervous system, 19,20 and also at the periphery. [21][22][23] Previous studies performed in our laboratory have revealed the existence of different serotonergic mechanisms that increase or inhibit sympathetic vascular and cardiac neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies have reported the occurrence of an interaction between adrenergic and serotonergic mechanisms in the central nervous system, 19,20 and also at the periphery. [21][22][23] Previous studies performed in our laboratory have revealed the existence of different serotonergic mechanisms that increase or inhibit sympathetic vascular and cardiac neurotransmission.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, a continual decline of cortical Ach concentration has been reported, which parallels the declining learning rate with aging (Feuerstein et al 1992). In contrast, no such age-related decline is known for norepinephrine (Allgaier et al 1995).…”
Section: Introductionmentioning
confidence: 89%
“…19,20). For autoinhibition-free electrical stimulation, the stimulation must not exceed 60 to 80 ms, because after this time, autoinhibition via ␣ 2 -autoreceptors begins (19).…”
Section: Superfusion Experimentsmentioning
confidence: 99%
“…Four stimulation periods were applied (S 1 to S 4 ); they began 75, 110, 145, and 180 min after start of superfusion. For evoking NE release free of autoinhibition, each stimulation period consisted of three trains of six pulses per 100 Hz, with a train interval of 1 min (pseudo-one-pulse conditions; see references 19,20). For autoinhibition-free electrical stimulation, the stimulation must not exceed 60 to 80 ms, because after this time, autoinhibition via ␣ 2 -autoreceptors begins (19).…”
mentioning
confidence: 99%